Silver doping of clinoptilolite particles enhances their effects on immunocompetent mammalian cells and inhibition of Candida albicans fungi - Solomiya Ya. Paryzhak; Tetiana I. Dumych; Olga Yu. Klyuchivska; Nazar O. Manko; Galyna V. Gryshchouk; Volodymyr O. Vasylechko; Rostyslav S. Stoika (Springer Nature, 2023)
The effects of natural clinoptilolite originated from the Transcarpathian region in the Western Ukraine and its composites doped with metal ions were studied toward: (1) cultured pseudo-normal mammalian cell and murine macrophages; (2) neutrophils of blood of healthy human donors; (3) mice immunized with model antigen; (4) mice under air-pouch model for estimation of microvasculature damage; (5) Candida albicans fungi. Silver doping enhanced cytotoxic action of natural clinoptilolite, while zinc doping did not do that. Clinoptilolite-Ag(NH3)2+ was non-toxic for murine macrophages and moderately toxic for human HEК293 cells. Toxicity of clinoptilolite-Ag+ composite toward HEК293 cells was comparable with the effect in positive control. Natural clinoptilolite and its silver derivatives enhanced the humoral immune response in mice and the levels of antibodies were comparable with such levels at response to standard adjuvant, which, however, damaged the microvasculature in mice. Furthermore, natural and Ag-enriched clinoptilolite were capable of activating neutrophils with a release of neutrophil extracellular traps. Finally, we showed that both clinoptilolite-Ag(NH3)2+ and clinoptilolite-Ag+ possessed much higher antifungal activity toward Candida albicans compared to such activity of the nonmodified clinoptilolite, while their doping with zinc did not show such enhancement. Thus, the Transcarpathian clinoptilolite possesses low toxicity toward mammalian cells and activates neutrophils in vitro, while silver doping enhanced the cytotoxicity of this material. Silver-doped derivatives demonstrated stimulating action on antibody production and the antifungal effect. Thus, the developed clinoptilolite-based composites are perspective for use as novel natural immuno-stimulators and antifungal agents.
Keywords: Clinoptilolite; Cytotoxicity; Immune-stimulation; Antifungal activity